Protecting Vietnam’s Sovereignty Over Sea And Islands – From The View Of Ho Chi Minh - Hiep, Assoc. Prof. Dr. Nguyen Van; Tram, Assoc. Prof. Dr. Pham Ngoc (The journal of contemporary issues in business and government, 2021)
Research on the protection of sea and island sovereignty according to Ho Chi Minh-style ideology is an issue that is of particular concern to the political and scientific circles at home and abroad because the dispute over sovereignty over the sea and islands in the South China Sea is increasingly complicated and drastic. The article has focused on reflecting the issues of sea and island sovereignty protection - from the perspective of Ho Chi Minh; affirming Vietnam's stance: independence, sovereignty, territorial integrity are sacred inalienable rights. The issue of protecting sovereignty in general, sovereignty of sea and islands in particular according to Ho Chi Minh is to uphold the above constant principle with the motto, and flexible method; with morality and style of President Ho Chi Minh: for the sake of the nation, conscientious, lifelong for the people for the country.